Social Studies Learning in Elementary Schools Based on Character Education - Riang Tati*, Andi; Pada, Amir (Riwayat: Educational Journal of History and Humanities, 2024)
This research aims to determine the role of social studies learning in creating students with character. The writing method used is literature review using books and articles that have similar themes as references. Based on the results of the literature review, the findings in this paper are that social studies learning has an important role in realizing students from an early age (elementary school level). The PBL model is a learning model that is very relevant in integrating character values in social studies learning in elementary schools.